CANCER, SIDE EFFECTS OF CHEMOTHERAPY AND NURSİNG CARE - Çiçek SARUHAN (International Journal of Health Services Research and Policy, 2020)
Cancer is a complex disease that emerges from uncontrolled cell growth as a result of genetic and environmental factors. Although there are various types of cancer and standard procedures are applied to specific types of cancers, it is also a personal disease. Cancer treatment varies depending on the cancer type, placement, stage, general health of the individual and other factors. Furthermore, cancer treatment is complex, costly and requires a long time. As the prevalence of cancer increased in societies, the application of systemic chemotherapy and the occurrence of associated side effects also increased. Early monitoring and assessment has become important for early diagnosis of side effect symptoms and reduction and prevention of complications through symptom control. Social environments and families should be taken into consideration during patient assessment. Monitoring and assessment of cancer patients by all healthcare professionals and nurses during chemotherapy is at least as important as the follow-up of disease. In this review, we aim to assess the factors leading to cancer, chemotherapy used to treat cancer and side effects associated with chemotherapy and to examine the applicable nursing care practices.